2019
DOI: 10.1111/pan.13758
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided erector spinae plane block for postoperative analgesia in pediatric patients undergoing splenectomy: A prospective randomized controlled trial

Abstract: Background: Many analgesic modalities have been investigated in pediatrics. We studied the analgesic efficacy of bilateral ultrasound-guided erector spinae plane block in pediatric patients undergoing open midline splenectomy.Methods: Sixty patients aged 3-10 years were randomly assigned into two groups:Control group received general anesthesia with bilateral sham erector spinae plane block using 0.3 mL/kg normal saline on each side. Erector spinae plane block group received bilateral ultrasound-guided erector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…However, a recent cadaver study revealed that local anesthetics did not spread to the dorsal anterior branch in most cases [24]. Despite the uncertain mechanism of action, ESPB has been widely used as postoperative analgesic over the last few years, and it seems to have achieved satisfactory results [25][26][27]. A previous meta-analysis [28] demonstrated that ESPB is an effective strategy to improve postsurgical analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent cadaver study revealed that local anesthetics did not spread to the dorsal anterior branch in most cases [24]. Despite the uncertain mechanism of action, ESPB has been widely used as postoperative analgesic over the last few years, and it seems to have achieved satisfactory results [25][26][27]. A previous meta-analysis [28] demonstrated that ESPB is an effective strategy to improve postsurgical analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…This ‘happily accidental’ block has been compared with other neuraxial techniques such as the epidural and paravertebral block and may prove to be a safer alternative 4. Although the ESP block has been successful in the adult population, there are only 42 documented cases (as of December 2019) in neonates, infant, and children 5–14. Despite the increasing number of indications for the ESP block, the anatomy, mechanism of action, concentration, and volume of anesthetic is yet to be determined especially in neonates and children 3 5…”
Section: Introductionmentioning
confidence: 99%
“…ESP block has been used as an alternative to neuraxial blocks for a wide range of procedures 5,6,8,17,25‐32 . Further investigations are needed to be performed in a larger sample size to determine whether 0.3‐0.5 mL/kg provides adequate dermatomal spread in infants and children; whether “in‐plane” or “out‐of‐plane” improves spread; or whether needle insertion over the lateral tip of the transverse process affects the cranio‐caudal spread as opposed to needle placement deep to the erector spinae muscle between the transverse processes.…”
Section: Discussionmentioning
confidence: 99%